Mobile healthcare services adoption. (2016) - Shanko, Genet; Negash, Solomon; Bandyopadhyay, Tridib
Recent penetration of mobile technologies opens exciting potential for e-healthcare in low-income countries - e-healthcare services can now reach the populations of rural and far away locations in a cost effective and timely manner. The final challenge however rests on successful user acceptance of the technologies of e-healthcare, which we investigate in this work. Our research enhance the basic TAM model with two additional context appropriate constructs from extant research to arrive at an extended TAM model that is suitable for understanding e-healthcare adoption in low-income countries. We operationalise the model with the help of a validated survey questionnaire in the health extensions workers of Ethiopia, a Sub-Saharan low-income country. Our result shows that compatibility positively affects adoption intention. These results demonstrate that inclusion of additional constructs of compatibility and network quality enhances the richness of the model and explain adoption intention in a more effective manner.